Simulasi dan Pembelajaran Routing Protocol dengan Metode EIGRP IPv4 untuk Mahasiswa Berbasis Web - Febrianto Halim Hadinoto; Agustinus Noertjahyana; Kristo Radion Purba (Jurnal Infra, 2018)
Students of Informatics need to understand about the parts of the Internet network and within their own Internet network with certain routing protocol methods so that the data packets sent become more clear and the routing protocol can find the lightest route in sending the data packets to the destination address. Routing Protocol itself is a process to determine the fastest path and advantageous location towards the intended search. One of the routing protocols currently used is the EIGRP (Enhanched Interior Gateway Routing Protocol) method not all students understand about this material. With this problem the authors create a website that concerns the EIGRP Routing Protocol.This website serves to help understand the students about Routing Protocol, especially EIGRP. The website has materials, quizzes, and simulators aimed at helping students to deepen how the EIGRP Routing Protocol works.Results resulting from this Website are students can better understand about EIGRP Routing Protocol by implementing simulator on Website. Simulator can check IP, subnet, and AS EIGRP well. Access to search the database on Admin can be in various formats is CSV, Excel, and PDF.